Effect of continuous nursing on quality of life and pain management of patients with cancer pain - Yu, Xiaolei; Li, Wenxin; Li, Qingshan (Nepalese Journal of Cancer, 2022)
Objective: To analyze the effect of multi-directional continuous nursing on improving the quality of life of patients with cancer pain after discharge.Methods: According to the method of random number table, 80 patients with cancer pain were divided into control group and intervention group, with 40 patients in each group. The control group received routine nursing and the intervention group received multi-directional continuous nursing. The quality of life of the two groups before and after nursing were compared and observed, and the satisfaction score was investigated.Results: The quality of life in the intervention group was higher than that in the control group (P